2016
DOI: 10.21831/cp.v35i3.10429
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Model Supervisi Klinis Berbasis Informasi Dan Teknologi

Abstract: Abstrak: Penelitian ini bertujuan mengembangakan model supervisi klinis berbasis informasi dan teknologi,  metode yang digunakan adalah reseacrh dan development (R&D),  meliputi tahap: research and information collecting,  planning, develop preliminary form of product, preliminary field testing. main product revision, main field testing, operational product revision, operational field testing, final product revision, dissemination and implementation Temuan Hasil penelitian berdasarkan tahapan R&D: pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
7
0
4
Order By: Relevance
“…Sedangkan kata "vision" berarti mengandung makna kemampuan untuk menyadari sesuatu tidak benar-benar terlihat. Sedangkan menurut (Rugaiyah, 2016) kegiatan supervisi adalah upaya memperbaiki dan mengontrol segala aktivitas agar terlakasana secara optimal. Ini bertujuan untuk memastikan kegiatan secara efektif dilaksanakan oleh mereka yang bertanggung jawab untuk melakukannya.…”
Section: Kajian Pustakaunclassified
“…Sedangkan kata "vision" berarti mengandung makna kemampuan untuk menyadari sesuatu tidak benar-benar terlihat. Sedangkan menurut (Rugaiyah, 2016) kegiatan supervisi adalah upaya memperbaiki dan mengontrol segala aktivitas agar terlakasana secara optimal. Ini bertujuan untuk memastikan kegiatan secara efektif dilaksanakan oleh mereka yang bertanggung jawab untuk melakukannya.…”
Section: Kajian Pustakaunclassified
“…Stage the first, namely the Pre Conference (early meeting). The preconference begins with the arrival of the PJOK teacher (Ansori et al, 2016) to the room the principal (Rugaiyah, 2016) to consult regarding the clinical supervision process to be implemented in fifth grade on PJOK subjects. This meeting discussed the implementation time and teacher readiness in implementing PJOK learning with the principal as a supervisor.…”
Section: Implementation Of Clinical Supervision At Mis Al Ittihadiyah...mentioning
confidence: 99%
“…Conventional supervision methods are still considered to have many obstacles to the problem of the time of service provided by the principal and school supervisor, virtual supervision provides access for teachers to convey inputs that are directly related to the learning process, through discussion expected to be able to solve teacher problems based on results the results of the study to improve the quality of education in schools. The results of another study by Rugaiyah (2016) suggested a clinical supervision model that school supervisors developed from Glickman's theory, including: i. final product revision; make the final revision as a whole after the implementation of clinical supervision activities in the field. j. dissemination and implementation; submit reports on the implementation of activities in a research seminar and scientific journal.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%